2015
DOI: 10.4269/ajtmh.15-0090
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Demographic and Clinical Characteristics of Syrian and Turkish Patients with Cutaneous Leishmaniasis

Abstract: Abstract. Cutaneous leishmaniasis (CL) is a significant public health problem with increasing incidence, especially in extreme circumstances. In this study, we compared the sociodemographic and clinical characteristics of 685 Syrian CL patients afflicted by the Syrian conflict and 685 Turkish CL patients in 2012. Patient age, gender, duration of disease, lesion size, type, and localization were evaluated. The duration of CL disease in Syrian CL patients (4.5 ± 4.3 weeks) was shorter than that of Turkish CL pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
9
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
5
9
1
Order By: Relevance
“…The head and neck region and also the upper extremities were determined to be the most frequent areas of the lesions in the previous studies. [3][4][5][6][7][8] Consistent with these findings, the majority of the lesions were located on the face and extremities in our patients. This finding was not a surprise, as the sandfly could easily bite the uncovered areas of the body at nighttime.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The head and neck region and also the upper extremities were determined to be the most frequent areas of the lesions in the previous studies. [3][4][5][6][7][8] Consistent with these findings, the majority of the lesions were located on the face and extremities in our patients. This finding was not a surprise, as the sandfly could easily bite the uncovered areas of the body at nighttime.…”
Section: Discussionsupporting
confidence: 87%
“…In the studies conducted in Turkey after the beginning of the civil war, it was found out that more than 50 % of the patients were younger than 20 years. [4][5][6]8 Consistent with the literature, most of the patients in this study were children and young adults. This finding suggests inadequate hygiene practices among these age groups especially due to the war conditions, higher exposure to the sandfly bites due to their higher stay in rural areas and spending more time outdoors and low immunity due to lack of exposure with the cause of the disease.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations